2014
DOI: 10.2174/138920021501140218125020
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Flavonoids in Human: A Comprehensive Review

Abstract: Flavonoids are naturally occurring polyphenols, which are widely taken in diets, supplements and herbal medicines. Epidemiological studies have shown a flavonoid-rich diet is associated with the decrease in incidence of a range of diseases. Pharmacological evidences also reveal flavonoids display anti-oxidant, anti-allergic, anti-cancer, anti-inflammatory, anti-microbial and anti-diarrheal activities. Therefore, it is critical to study the biotransformation and disposition of flavonoids in human. This review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 0 publications
4
138
0
Order By: Relevance
“…In contrast to in vitro studies, it is indeed possible that flavonoids do not directly modulate antioxidant activity in vivo, as they appear to be extensively metabolized and their metabolites may not be very effective as free radical scavengers (Chen et al, 2014;Rodriguez-Mateos et al, 2014). However, flavonoids and their metabolites may promote upregulation of antioxidant enzymes such as catalase, glutathione peroxidase and superoxide dismutase, whose biological activity may efficiently contribute to prevent oxidative insults (Halliwell and Gutterridge, 2003).…”
Section: Effects Of Dietary Flavonoids On Redox Status and Moultmentioning
confidence: 99%
“…In contrast to in vitro studies, it is indeed possible that flavonoids do not directly modulate antioxidant activity in vivo, as they appear to be extensively metabolized and their metabolites may not be very effective as free radical scavengers (Chen et al, 2014;Rodriguez-Mateos et al, 2014). However, flavonoids and their metabolites may promote upregulation of antioxidant enzymes such as catalase, glutathione peroxidase and superoxide dismutase, whose biological activity may efficiently contribute to prevent oxidative insults (Halliwell and Gutterridge, 2003).…”
Section: Effects Of Dietary Flavonoids On Redox Status and Moultmentioning
confidence: 99%
“…Based on the above reasons, we proposed the change of metabolic profiles of catalpol and acteoside in CKD rats compared with that in normal rats after oral administration of R. glutinosa extract might be due to the reduced metabolic enzymes in the CKD state. Additionally, it has been widely reported that glycosides in orally administrated medicines usually could be metabolized by intestinal bacteria before absorption into blood [26][27][28]. Marked alteration of the colonic bacterial flora was also observed in humans and animals with advanced CKD [29].…”
Section: Analysis Of the Absorption And Excretion Constituents Ofmentioning
confidence: 99%
“…One reason for this is the very limited commercial availability of metabolites for experimental testing. There are three major types of metabolic derivatives of flavonoids formed as a consequence of enzymatic conjugation with methyl-, sulfate-or glycuronyl groups in the small intestine and liver catalyzed by COMT, sulfotransferase (SULT) or UDP-glucuronosyltransfrease (UGT), respectively (19,20,42). Considering some structural modification Table I.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these polyphenols can express antiproliferative, cytotoxic, proapoptotic, antiinvasive, antimetastatic, antiangiogenic and antiinflammatory properties in different cancer cell lines or animal models (17). However, it is well known that in the human body, flavonoids undergo an extensive metabolism and as a result of this conversion only different metabolic conjugates enter the circulatory system and can reach target malignant tissue (18,19). Differently from parent flavonoids, current knowledge about the possible anticancer action of their metabolites is still rather limited making the prediction of bioactive behavior of flavonoids in the human body complicated.…”
Section: Introductionmentioning
confidence: 99%